Pengaruh Pendidikan Kesehatan dengan Media Audio Visual terhadap Peningkatan Pengetahuan Masyarakat Dusun Batu Merah B Terkait ISPA - Karol Octrisdey; Made Susilawati; Meliance Bria; Melkianus Ratu; Handrianus Akoit; Veronika Nitsae; Ahmad Mumtaz Tauba (Pusat riset dan Inovasi Nasional, 2025)
Acute Respiratory Tract Infection (ARI) is a health problem that still occurs frequently, especially in areas with limited access to health information and knowledge. One effort that can be made to overcome this problem is by providing health education to the community. Health education conducted using interesting and easy-to-understand media, such as audio-visual media, has been proven to be able to increase public understanding more effectively. This study aims to determine the effect of the use of audio-visual media in health education on increasing the knowledge of the Batu Merah B Hamlet community regarding ARI. This study used a quasi-experimental design with a one-group pretest-posttest approach, in which 50 people were selected purposively as the research sample. Data were collected using questionnaires before and after the health education intervention using audio-visual media. Data analysis was performed using the Wilcoxon test to examine differences in knowledge before and after the intervention. The results showed a significant increase in knowledge after the health education intervention (p < 0.05). The average score of community knowledge increased from 60.2 in the pretest to 83.5 in the posttest. This improvement demonstrates the effectiveness of audiovisual media in conveying information related to acute respiratory infections (ARI) and facilitates public understanding and retention. Therefore, it is recommended that health education using audiovisual media be used more widely in health promotion activities to achieve better results and accelerate changes in public health behavior. Health education using audiovisual media also provides a more interactive and engaging learning experience, thereby increasing community engagement in the learning process.